Gaya Retorika Habib Bahar Bin Smith Dalam Media Youtube - Muzakki, M. Athallah Ariq; Ridwan, Aang; Rustandi, Ridwan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The objective of this research is to analyze the rhetorical style of Habib Bahar, his gestures and facial expressions, as well as his performance in delivering his dakwah (Islamic preaching) through YouTube. The approach used in this study is descriptive qualitative. The results of this research indicate that: (1) Habib Bahar uses an informal language style in his preaching. (2) Habib Bahar has distinctive gestures and facial expressions when delivering his message. (3) Habib Bahar demonstrates strong performance and enthusiasm in conveying the truth of Islamic teachings in his dakwah.